2020
DOI: 10.1016/j.gaitpost.2019.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Classifying neck pain status using scalar and functional biomechanical variables – development of a method using functional data boosting

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Out of the total of 27 studies that were identified for the topic of pain, 14 used a prospective cohort design, 197 198 199 200 201 202 203 204 205 206 207 208 209 210 11 used an observational design, 200 204 205 207 210 211 212 213 214 215 216 6 used a retrospective cohort design, 211 214 215 217 218 219 4 used a randomized control trial, 201 212 220 221 1 used a cross-sectional design, 222 and 1 used mixed methods. 223 Most studies used questionnaire/survey data, but eight used administrative databases, 206 207 208 210 212 220 221 222 seven used mobile devices/sensors, 200 203 204 205 210 216 220 and four used a data warehouse or registry. 198 203 208 214 Study populations were mostly done with adults in the outpatient setting but four were inpatient 197 201 211 223 and one was done with a pediatric population.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Out of the total of 27 studies that were identified for the topic of pain, 14 used a prospective cohort design, 197 198 199 200 201 202 203 204 205 206 207 208 209 210 11 used an observational design, 200 204 205 207 210 211 212 213 214 215 216 6 used a retrospective cohort design, 211 214 215 217 218 219 4 used a randomized control trial, 201 212 220 221 1 used a cross-sectional design, 222 and 1 used mixed methods. 223 Most studies used questionnaire/survey data, but eight used administrative databases, 206 207 208 210 212 220 221 222 seven used mobile devices/sensors, 200 203 204 205 210 216 220 and four used a data warehouse or registry. 198 203 208 214 Study populations were mostly done with adults in the outpatient setting but four were inpatient 197 201 211 223 and one was done with a pediatric population.…”
Section: Resultsmentioning
confidence: 99%
“…Studies explored various outcomes including surgical applications such as determination of postsurgical measures based on residual pain, 197 predicting patellofemoral pain 1 year after intervention, 201 predicting neuropathic pain, 202 predicting chronic pain of 7 to 10 years into the future, 217 predicting complex regional pain syndrome, 207 predicting pain relief for knee osteoarthritis patients, 209 detection of pain, 210 214 216 222 and pain intensity estimation/classification. 205 213 215 220 Other outcomes focused on pain as a predictor of anxiety and depression, coronary heart disease, 199 health status, 218 noncancer pain as predictor of brain aging, 208 and length of stay. 211 For patients with low back pain, societal cost, 212 and clinical and sociodemographic predictors of increased disability 221 have been studied.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional variables are typically temporal and/or spatial variables, where each observation for each variable can take on multiple values [33]. The most common example of functional variables would be kinematic and muscle activation data, which are temporal variables [34,35]. Less common functional variables are cortical activation patterns and radiological images [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…These properties make CWB a powerful method at the intersection of (explainable) statistical modelling and (black-box prediction) machine learning. For this reason, CWB is frequently used in medical research, e.g., for oral cancer prediction (Saintigny et al, 2011), detection of synchronization in bioelectrical signals (Rügamer et al, 2018), or classifying pain syndromes (Liew et al, 2020). In contrast, many other gradient boosting methods such as XGBoost (Chen and Guestrin, 2016) solely focus on predictive performance and (mainly) use tree-based base learners with higher-order interactions.…”
Section: Introductionmentioning
confidence: 99%